A Road Map for Conservation, Use, and Public Engagement around North America’s Crop Wild Relatives and Wild Utilized Plants - Khoury, Colin K.; Greene, Stephanie L.; Krishnan, Sarada; Miller, Allison J.; Moreau, Tara (Wiley, 2019)
Crop wild relatives—the plant species closely related to agricultural crops—are valuable genetic resources used by plant breeders to increase pest and disease resistance, stress tolerance, nutritional profile, and other traits critical to productivity, quality, and sustainability. Wild utilized plants provide food and a variety of other ecosystem and cultural services to people. North America harbors a rich native flora that includes wild relatives of important food, fiber, industrial, feed and forage, medicinal, and ornamental crops, as well as a diversity of regionally significant wild utilized plants. Many of these species are threatened in their natural habitats, and most are underrepresented in plant genebanks and botanical gardens. These conservation gaps limit the portfolio of useful plant diversity available to present and future generations. Likewise, the myriad potential uses of North American crop wild relatives and wild utilized plants are underexplored, and public awareness of their value and threats is limited. Greater coordination of efforts among plant conservation, land management, agricultural science, and botanical education and outreach organizations will be necessary to secure, enhance use, and raise awareness with regard to these species. A road map for collaborative action is presented here, focused on five priorities: (i) to understand and document North America’s crop wild relatives and wild utilized plants, (ii) to protect threatened species in their natural habitats, (iii) to collect and conserve ex situ the diversity of prioritized species, (iv) to make this diversity accessible and attractive for plant breeding, research, and education, and (v) to raise public awareness of their value and the threats to their persistence.